BUILDING MARKETING UNTUK KOMUNITAS SENDIRI BERBASIS ONLINE - Padeli Padeli; Sudaryono Sudaryono; Indri Handayani (CCIT Journal, 2014)
World wide web or web is often called one of the internet facilities are becoming increasingly well known that many people often view it as the only way to surf the internet. By having a website or a homepage means a community has its own place on the web, in which all people worldwide the opportunity to redirect the browser and find out more about what is published. In order to attract and keep visiting the website design and loading required and information is good news. This is an opportunity that should be best utilized to inform or whatever is the superior product and service profile for a company or agency that wants more widely known. Internet is the best solution to find information quickly and efficiently, and therefore the sale is a web-based online media that are considered practical because people do not need to come directly to find the desired item. The conclusion of this study are as follows: 1. This program can provide convenience to consumers in finding and buying products sold by Bizarre Sounds Production, sales order, booking and information service for the better stuff. 2. The information displayed is not just news-news about the world of metal music but also the latest promotions Bizarre Sounds Production of products in order to increase sales and profits of the company.